2011
DOI: 10.3406/revec.2011.1584
|View full text |Cite
|
Sign up to set email alerts
|

Évolution de la population nicheuse de l’Érismature à tête blanche Oxyura leucocephala sur le lac Tonga (Algérie)

Abstract: L’Érismature à tête blanche Oxyura leucocephala est une espèce classée dans la liste rouge de l’UICN comme menacée, elle est également protégée par la législation algérienne en tant qu’espèce menacée de disparition. Basé sur les recensements hebdomadaires des adultes, mâles et femelles, et des nichées (ou familles) sur le site Ramsar du Lac Tonga, site de nidification le plus important de l’espèce sur la rive sud de Méditerranée, notre travail cherche à actualiser l’état de cette population afin d’élabor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Our data provide a detailed overview of Laro-limicolae phenology at inter-annual and intra-seasons and highlight the importance of the El Kala wetland complex. Although the data are incomplete, previous studies showed that the region is the major site in Algeria for migrating waterbirds (Ochando and Jacobs, 1978;Boumezbeur, 1993;Lazli et al, 2011aLazli et al, , 2011bLazli et al, 2012;Gherib and Lazli, 2017;Menasria and Lazli, 2017). Similar to the other Algerian coastline wetlands, this region has also proved to be a favourable location for Laro-limicolae, which remain little studied (Seddik, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our data provide a detailed overview of Laro-limicolae phenology at inter-annual and intra-seasons and highlight the importance of the El Kala wetland complex. Although the data are incomplete, previous studies showed that the region is the major site in Algeria for migrating waterbirds (Ochando and Jacobs, 1978;Boumezbeur, 1993;Lazli et al, 2011aLazli et al, , 2011bLazli et al, 2012;Gherib and Lazli, 2017;Menasria and Lazli, 2017). Similar to the other Algerian coastline wetlands, this region has also proved to be a favourable location for Laro-limicolae, which remain little studied (Seddik, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…1). Due to the richness and diversity of its habitats, it is a renowned wintering and breeding site for a multitude of waterbird species, some of which are rare and declining in range, such as the white-headed duck Oxyura leucocephala and the marbled teal Marmaronetta angustirostris (Boumezbeur, 1993;Lazli et al, 2011aLazli et al, , 2011bLazli et al, , 2012Menasria and Lazli, 2017;Mecif et al, 2020;Gherib et al, 2021).…”
Section: Study Areamentioning
confidence: 99%
“…The Aythya nyroca is a very abundant diving duck in Lake Tonga (Aissaoui et al, 2009(Aissaoui et al, , 2011Lazli et al, 2011a). Its phenology was monitored over an entire annual cycle, from September 2020 to August 2021, with one outing every two weeks.…”
Section: Materials and Methods (Optional)mentioning
confidence: 99%
“…Despite the existence of various works on Algerian aquatic avifauna, in particular, Anatidae, Rallidae, and Podicipedidae (Boumezbeur, 1993;Lazli et al, 2011aLazli et al, , b, 2014Gherib, Lazli, 2017;Menasria, Lazli, 2017;Lazli et al, 2018;Bediaf et al, 2020; POPULATION DYNAMICS AND WINTERING BEHAVIOR OF BLACK-HEADED GULL Chroicocephalus ridibundus AT EL MELLAH LAGOON (NORTHEASTERN ALGERIA) Benmetir et al, 2020;Mecif et al, 2020;Ziani et al, 2020;Gherib et al, 2021), few studies have been devoted to seabirds, which have so far received very little attention from researchers. Recent information on this subject is limited to occasional observations and local or global syntheses (Jacob, Coubet, 1980;Ledant et al, 1981;Doumandji et al, 1988;Hamza, Slimani, 1990;Thibault, 1993;Benyacoub, Chabi, 2000;Isenmann, Moali, 2000;Boukhroufa, 2001;Brahmia, 2002;Moulaï, 2006;Bougaham, Moulaï, 2013).…”
Section: Introductionmentioning
confidence: 99%